2020
DOI: 10.1101/2020.11.28.401471
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Translesion DNA synthesis-driven mutagenesis in very early embryogenesis of fast cleaving embryos

Abstract: In early embryogenesis of fast cleaving embryos DNA synthesis is short and surveillance mechanisms preserving genome integrity are inefficient implying the possible generation of mutations. We have analyzed mutagenesis in Xenopus laevis and Drosophila melanogaster early embryos. We report the occurrence of a high mutation rate in Xenopus and show that it is dependent upon the translesion DNA synthesis (TLS) master regulator Rad18. Unexpectedly, we observed a homology-directed repair contribution of Rad18 in re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
(136 reference statements)
0
2
0
Order By: Relevance
“…It has been observed that during the very early stage of Xenopus embryonic development, the HDR activity of Rad18 is coupled to its TLS activity, through PCNA mUb , thereby reducing the mutational load introduced. This mechanism adds up to the MMR activity that corrects mismatches introduced by TLS [ 73 ]. Taking into consideration this observation, it is possible that, in vivo, the mutagenesis rate of TLS Pols may be underestimated due to the concerted action of Rad18 repair activity.…”
Section: The Crucial Role Of Tls To Tolerate Structural Impediments During Dna Replicationmentioning
confidence: 99%
“…It has been observed that during the very early stage of Xenopus embryonic development, the HDR activity of Rad18 is coupled to its TLS activity, through PCNA mUb , thereby reducing the mutational load introduced. This mechanism adds up to the MMR activity that corrects mismatches introduced by TLS [ 73 ]. Taking into consideration this observation, it is possible that, in vivo, the mutagenesis rate of TLS Pols may be underestimated due to the concerted action of Rad18 repair activity.…”
Section: The Crucial Role Of Tls To Tolerate Structural Impediments During Dna Replicationmentioning
confidence: 99%
“…Additionally, cold sock causes the opening of interchain disulfide bridges in protamines that may interfere with sperm DNA [ 9 ]. DNA integrity is necessary for embryo development [ 10 ]. Higher sperm SDF resulted in lower fertilization rates [ 11 ], lower pregnancy rate [ 12 ], and finally, lower pregnancy rate [ 3 ].…”
Section: Introductionmentioning
confidence: 99%